2021
DOI: 10.1177/21582440211061373
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Intention and Purchase of Health Insurance Among Malaysian Working Adults

Abstract: This study explored the effects of insurance literacy, perceived usefulness, attitude toward health insurance, subjective norm, and perceived behavioral control on the intention to purchase and the actual purchase of health insurance among working adults in Malaysia. This quantitative study adopted the cross-sectional design with data gathered from 1,308 working adults through a Google form link shared in social media. Upon analysis, the outcomes revealed that insurance literacy, perceived usefulness, attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 98 publications
2
19
1
4
Order By: Relevance
“… 37 According to Mamun et al, intention is a predictor of someone subscribing to health insurance. 38 This is in line with the results of this study that intention is a predictor of someone to comply with paying health insurance premiums.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 37 According to Mamun et al, intention is a predictor of someone subscribing to health insurance. 38 This is in line with the results of this study that intention is a predictor of someone to comply with paying health insurance premiums.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is also different from other researchers, who say that the benefits of health insurance, attitudes, subjective norms and perceived behavioral control are the determinants of customer intentions to buy health insurance. 38 This finding is also different from the findings of Aprianti who said factors which are related to someone’s intention to consume iron tablets in young women are perceived threats, perceived benefits, perceived barriers and perceived self-efficacy. 39 …”
Section: Discussioncontrasting
confidence: 67%
“…Residents' purchase of commercial health insurance is a type of consumer purchasing decision, and there is an influence mechanism similar to that for general purchase behavior. Many studies have explored the influencing factors of commercial health insurance demand (Atinga et al 2015;Mamun et al 2021;Abdel Fattah et al 2021). The existing literature mainly focuses on three aspects: demographic characteristics, and subjective and objective influencing factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Study results from [5] revealed that perceived usefulness and perceived risk were the key factors in determining attitudes towards the intention to purchase health insurance. According to [6] in their quantitative study, the results showed that perceived usefulness, insurance literacy, subjective norm, attitude towards health insurance, and perceived behavioural control had a significant positive influence on the intention to purchase health insurance.…”
Section: Introductionmentioning
confidence: 99%